2009
DOI: 10.1097/pcc.0b013e318198b012
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia and insulin therapy in the critically ill child*

Abstract: This survey suggests significant variation in the management of hyperglycemia across the UK Practice varies even among intensivists from the same unit, reflecting the fact that few units have 'an agreed written guidance in place.' The majority of intensivists would be prepared to participate in a trial of tight glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Similar to findings by others, we report that most pediatric ICU practitioners (60%) believe that hypo glycemia is more dangerous than hyper glycemia in critically ill children [24,25]. Although there are reports of immediate and long-term sequela from hypoglycemic episodes in children, the direct relationship of the severity and duration of hypoglycemia to adverse effects is unclear.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Similar to findings by others, we report that most pediatric ICU practitioners (60%) believe that hypo glycemia is more dangerous than hyper glycemia in critically ill children [24,25]. Although there are reports of immediate and long-term sequela from hypoglycemic episodes in children, the direct relationship of the severity and duration of hypoglycemia to adverse effects is unclear.…”
Section: Discussionsupporting
confidence: 82%
“…Despite recent debate regarding outcome improvements in adults and goal target glycemic ranges, numerous medical advisory groups recommend routine glycemic control as standard care in adult ICUs [19-22]. Because previous studies suggest most pediatric intensivists believe hyperglycemia may be hazardous to their patients, readers may infer that as in adult ICUs, glycemic control measures are the norm in pediatric ICU practice [24,25]. To ascertain the true practice patterns regarding glycemic control in critically ill children, we assessed beliefs and actual practice habits in a spectrum of pediatric ICUs in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey among the pediatric intensivists in the UK [29], and a pros-pective study from the PICUs of Australia and New Zealand [30] showed neither uniform glucose con-trol regimes nor consensus regarding levels of hyper-glycemia requiring therapy.…”
Section: Evidence In Critically Ill Childrenmentioning
confidence: 99%